A comparative study of dermatoglyphic markers in schizophrenia patients and normal controls - Latiff, Ashma A.; S., Sundarapandian; R., Arul Saravanan (International Journal of Research in Medical Sciences, 2017)
Background: Schizophrenia is a complex mental illness with multiple etiological factors. Prenatal insult to the developing foetus has been implicated as a major risk factor for the genesis of schizophrenia, according to the neuro-developmental model. As the brain and skin are ectodermal derivatives, insult to developing brain is reflected in several dermatoglyphic markers. Methods: Total finger ridge count (TFRC), Total A-B ridge count (TABRC) and ATD Angle of 100 patients diagnosed with schizophrenia were compared with 100 age and sex matched healthy controls. Results: Statistically significant differences were observed in the values recorded and compared between healthy controls and schizophrenia patients. Conclusions: This study shows the correlation between abnormalities in dermatoglyphic patterns and development of schizophrenia.